Study of Bioactive Content Liberica Coffe Powder (Coffea liberica. Var) and Bajakah Tampala Roots (Spatholobus littoralis) Growing in Peatland Using GC- MS - Saputera, Saputera; Setyowati, Erni Dwi Puji; Mahendra, Wayan Riki; Zulkifly, Rahmad (Agroindustrial Journal, 2024)
Liberica coffee (Coffee liberica Var.)  is known as a typical peatland coffee because of its ability to adapt to peat soils compared to other types of coffee. The bajakah tampala plant (Spatholobus littoralis Hassk) is a plant from the genus Spatholobus. The roots of the bajakah tampala are used empirically as medicine by the Dayak community. Based on hereditary experience, boiled water from bajakah tampala root can be used as a medicine for stomach pain, diarrhea, and dysentery. This plant contains phenolics, flavonoids, tannins and saponins so bajakah tampala can be used as herbal medicine. Until now, the active compound content of the combination of Liberica coffee and bajakah tampala root is unknown. Thus, this research aims to determine the bioactive content of Liberica coffee and bajakah tampala roots. This research was conducted using two factorials, Randomized Complete Block Design (RCBD), where Factor 1, consists of Liberica coffee powder concentrations, and Factor 2 consists of bajakah tampala powder concentrations. Each factor had 3 levels.  Bajakah tampala roots were sorted, washed, cut into small pieces, oven-dried at 50°C for 6 hours, ground, sieved using an 80 mesh, then weighed and ready to be used as an herbal coffee additive. Bajakah tampala was oven-dried at 50°C for 6 hours, ground, sifted, then mixed with Liberica coffee powder according to treatment groups (L1, L2, L3 and B1, B2, B3) for 9 combination treatments with 3 repetitions. Analysis of bioactive compounds in this research was determined using GC-MS. The analysis results show that 8 main components seen based on retention time, namely caffeine, hexadecanoic acid, palmitic acid, hexadecanoic acid, ethyl ester, octadec-9-enoic acid, octadecanoic acid, stearic acid, octadeca-9,12-dienoic acid methyl, 9,12-octadecadienoic acid (Z, Z)-Lino and ethyl linoleate. It is recommended that further research be carried out regarding the bioactive content of Liberica and bajakah coffee as herbal medicine.